(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
The interview with Walter Carlo sought to obtain data on possible distinctions among the learning, creation and performance processes experienced in circus between the 1940’s and 1990’s (period in which he acted as an artist) and those offered in professional schools, especially the Luiz Olimecha National Circus School (ENC) where he was a teacher between 1995 and 2018. It also addressed unique aspects of circus life, education and work in the mentioned period, such as the difficulty in accessing formal education, the methodologies and characteristics of artistic teaching in itinerancy and the workspaces beyond the big tops. The statement also brings information about the integration of elements from different arts in the circus scene and the resources most validated by this artist and his contemporaries in the ways of creating and inserting his acts in the market, offering a record of memory and artistic, cultural and social production of the Brazilian circus.